Transformasi Konstitusional Pertanggungjawaban Presiden Dalam Sistem Ketatanegaraan Indonesia Pasca Amandemen UUD 1945 - Rizki Rahayu Fitri; Agnes Fitryantica (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study examines the transformation of presidential accountability within Indonesia’s constitutional system following the amendments to the 1945 Constitution. The main issue addressed is how the mechanisms of presidential accountability have changed after the constitutional amendments and what implications these changes have had on Indonesia’s constitutional structure. This research employs a normative juridical method with a historical and comparative constitutional approach. The findings reveal a significant shift in the accountability model—from the President being accountable to the People’s Consultative Assembly (MPR) to being directly accountable to the people through general elections. This transformation has strengthened Indonesia’s presidential system, affirmed the principle of popular sovereignty, and altered the configuration of inter-institutional relations. However, the post-amendment framework has shown weaknesses in overseeing presidential power, raising concerns over potential abuse of authority. Therefore, it is essential to enhance the mechanisms of checks and balances to ensure the constitutional system continues to operate in line with democratic principles and constitutional supremacy.